J.P. Benjamin papers - Benjamin, J. P. (Judah Philip), 1811-1884.
ALsS and photocopies and typewritten transcripts of correspondence concerning Benjamin's years at Yale College, New Haven, Conn.; the rights of free African Americans in slave states; charges that Benjamin and Jefferson Davis profited from the Civil War; imprisonment of Davis; Confederate John J. McRae's voluntary exile in Belize; and Benjamin's exile and career in law in England. Correspondents include John C. Breckinridge, J.M. Mason, C.G. Memminger, and Simeon North.
In part, negative photocopy and typewritten transcripts.
U.S. senator from Louisiana, Confederate cabinet officer, and lawyer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Breckinridge, John C. -- 1821-1875 -- Correspondence; Davis, Jefferson, -- 1808-1889.; Mason, J. M. -- 1798-1871 -- Correspondence; McRae, John J., -- 1815-1868.; Memminger, C. G. -- 1803-1888 -- Correspondence; North, Simeon, -- 1802-1884 -- Correspondence; Yale College (1718-1887); African Americans -- Civil rights; American Confederate voluntary exiles -- Belize; American Confederate voluntary exiles -- England; Practice of law -- England; Slavery; United States -- History -- Civil War, 1861-1865.; Cabinet officers -- Confederate States of America; Lawyers; Senators, U.S. Congress -- Louisiana